A multi-assemblage, multi-metric biological condition index for eastern Amazonia streams. (July 2017) - Chen, Kai; Hughes, Robert M.; Brito, Janaina G.; Leal, Cecilia G.; Leitão, Rafael P.; de Oliveira-Júnior, José M.B.; de Oliveira, Vívian C.; Dias-Silva, Karina; Ferraz, Silvio F.B.; Ferreira, Joice; Hamada, Neusa; Juen, Leandro; et al.
Abstract: Multimetric indices (MMIs) are widely used for assessing ecosystem condition and they have been developed for a variety of biological assemblages. However, when multiple assemblages are assessed at sites, the assessment results may differ because of differing physiological sensitivities to particular stressor gradients, different organism size and guilds, and the effects of different scales of disturbances on the assemblages. Those differences create problems for managers seeking to avoid type-1 and type-2 statistical errors. To alleviate those problems, we used an anthropogenic disturbance index for selecting and weighting metrics, modeled metrics against natural variability to reduce the natural variability in metrics, and developed an MMI based on both fish and aquatic insect metrics. We evaluated eight different ways of calibrating and combining candidate metrics and found that MMIs with unweighted and modeled aquatic insect and fish metrics were the preferred MMI options.